Design of event conditions in event‐triggered control systems: a non‐fragile control system approach. Issue 9 (1st June 2016) - Yu, Hao; Hao, Fei
Abstract : This study investigates the design of event conditions in the event‐triggered control systems. The event‐triggered control systems are formulated as uncertain systems with non‐fragile controllers. Then, a non‐fragile control system approach is used to design the event conditions. Based on this approach, a new type of event conditions is proposed, which depends on the difference between a matrix induced 2‐norm and a vector Euclidian norm. It is shown that the proposed event condition is less conservative and leads to larger inter‐event times than those in some existing works. Furthermore, a method in terms of linear matrix inequality is proposed to design the parameters in the event conditions. Also, the case of non‐zero transmission delays is considered. Finally, a numerical example is provided to illustrate the efficiency and feasibility of the obtained results.